2017
DOI: 10.1523/jneurosci.0468-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual Modulation in Mouse Primary Visual Cortex Depends on Cross-Modal Stimulus Configuration and Congruency

Abstract: The sensory neocortex is a highly connected associative network that integrates information from multiple senses, even at the level of the primary sensory areas. Although a growing body of empirical evidence supports this view, the neural mechanisms of cross-modal integration in primary sensory areas, such as the primary visual cortex (V1), are still largely unknown. Using two-photon calcium imaging in awake mice, we show that the encoding of audiovisual stimuli in V1 neuronal populations is highly dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(125 citation statements)
references
References 63 publications
(35 reference statements)
10
109
6
Order By: Relevance
“…Overall, our results favor the traditional model of cortical multisensory processing, with separate cortical domains for each modality, and multisensory neurons being restricted to intermediate zones between these domains (e.g., Avillac, Ben Hamed, & Duhamel, ; Foxworthy, Clemo, & Meredith, ). Most of the physiological evidence for auditory influences on spiking activity in visual cortex have come from studies in mice (Iurilli et al., ; Meijer et al., ; Olcese et al., ), which have direction connections between the primary visual and primary auditory cortex (Meredith & Lomber, ), reflecting a general scaling rule whereby smaller brains tend to show more direct connectivity across cortical systems (HorvĂĄt et al., ; Rosa et al., ). Direct anatomical connections between the visual and auditory cortex in primates have been reported (Cappe & Barone, ; Falchier, Clavagnier, Barone, & Kennedy, ; Palmer & Rosa, , ; Rockland & Ojima, ), but to our knowledge, there is only one study that showed that auditory stimuli can modulate the spiking activity in the visual cortex of primates (Wang et al., ), producing a modest decrease in response latency in awake animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our results favor the traditional model of cortical multisensory processing, with separate cortical domains for each modality, and multisensory neurons being restricted to intermediate zones between these domains (e.g., Avillac, Ben Hamed, & Duhamel, ; Foxworthy, Clemo, & Meredith, ). Most of the physiological evidence for auditory influences on spiking activity in visual cortex have come from studies in mice (Iurilli et al., ; Meijer et al., ; Olcese et al., ), which have direction connections between the primary visual and primary auditory cortex (Meredith & Lomber, ), reflecting a general scaling rule whereby smaller brains tend to show more direct connectivity across cortical systems (HorvĂĄt et al., ; Rosa et al., ). Direct anatomical connections between the visual and auditory cortex in primates have been reported (Cappe & Barone, ; Falchier, Clavagnier, Barone, & Kennedy, ; Palmer & Rosa, , ; Rockland & Ojima, ), but to our knowledge, there is only one study that showed that auditory stimuli can modulate the spiking activity in the visual cortex of primates (Wang et al., ), producing a modest decrease in response latency in awake animals.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have now shown that low level sensory cortical areas, historically considered unisensory, can be influenced by other modalities (for a review see Ghazanfar & Schroeder, 2006). In particular, these studies have shown cross-modal influences in the auditory and visual systems (Bizley & King, 2008, 2009Bizley, Nodal, Bajo, Nelken, & King, 2007;Iurilli et al, 2012;Lakatos, Chen, O'Connell, Mills, & Schroeder, 2007;Meijer, Montijn, Pennartz, & Lansink, 2017;Olcese, Iurilli, & Medini, 2013;Schroeder & Foxe, 2002;Wang, Celebrini, Trotter, & Barone, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, area A1 sends axons to V1 where they connect to inhibitory interneurons (Iurilli et al, 2012). As summarized by Meijer and authors in their paper (Meijer et al, 2017), auditory stimuli suppress VIP interneurons which inhibit SOM cells which in turn suppresses PV (Parvalbumin; GABAergic interneurons) cells and distal dendrites (involved in non-local synapses) of supragranular pyramidal cells (Gentet, 2012;Meijer et al, 2017). This specific pathway is activated precisely in response only to non-visual inputs (Deneux et al, 2018).…”
Section: Inhibitory Mechanismsmentioning
confidence: 96%
“…Avillac et al, 2007;Foxworthy et al, 2013). Most of the physiological evidence for auditory influences on spiking activity in visual cortex have come from studies in mice (Iurilli et al, 2012;Olcese et al, 2013;Meijer et al, 2017), which have direction connections between the primary visual and primary auditory cortex (Meredith & Lomber, 2017), reflecting a general scaling rule whereby smaller brains tend to show more direct connectivity across cortical systems (HorvĂĄt et al, 2016;Rosa et al, 2018). Direct anatomical connections between the visual and auditory cortex in primates have been reported (Falchier et al, 2002;Rockland & Ojima, 2003;Cappe & Barone, 2005;Palmer & Rosa, 2006a, 2006b), but to our knowledge, there is only one study that showed that auditory stimuli can modulate the spiking activity in the visual cortex of primates (Wang et al, 2008), producing a modest decrease in response latency in awake animals.…”
Section: Implications For Multisensory Integration In the Cerebral Comentioning
confidence: 99%
“…However, studies have now shown that low level sensory cortical areas, historically considered unisensory, can be influenced by other modalities (for a review see Ghazanfar and Schroeder, 2006). In particular, these studies have shown cross-modal influences in the auditory and visual systems (Schroeder & Foxe, 2002;Bizley et al, 2007;Lakatos et al, 2007;Bizley & King, 2008, 2009Wang et al, 2008;Iurilli et al, 2012;Olcese et al, 2013;Meijer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%